Cash Receipt and Disbursement Accounting Information System: A Case Study at the Muhammadiyah AT Tanwir Mosque Banjarmasin - Monika Handayani; Muhammad Bahit; Hana Lutfita (Proceeding of The International Conference on Economics and Business, 2023)
Cash receipts and disbursements in the context of a mosque or religious institution have special characteristics that are different from commercial businesses or other non-profit organizations. Good management of cash receipts and disbursements in mosques is key to maintaining financial stability, functioning as an effective religious and social center, and fulfilling the social and humanitarian duties set by Islam. This also builds congregational trust and support which is crucial in running a mosque successfully. This research aims to determine the appropriate and effective Cash Receipts and Disbursements Accounting Information System at the Muhammadiyah Mosque A T Tanwir Banjarmasin. This research uses a case study approach to receiving and disbursing cash at the mosque. The results of this research found that all recording of cash receipt and disbursement transactions at the Muhammadiyah At Tanwir Banjarmasin Mosque still uses a semi-computerized system. The author suggests using a cash receipt and disbursement application program using PHP to help the Muhammadiyah At Tanwir Banjarmasin Mosque record transactions and create cash receipt and disbursement reports